The Role of Cyber Security in Promoting Digital Inclusion: A Case Study of Pakistan - Mehmood, Muhammad (Annals of Human and Social Sciences, 2025)
This article explores the essential role of cybersecurity in fostering digital inclusion in Pakistan, a country striving to harness the digital revolution for socio-economic progress. Digital inclusion, ensuring equitable access to technology and services, is a key driver of development. However, Pakistan faces significant barriers such as cyber threats, infrastructure gaps, and the lack of comprehensive legislation, which erode trust in digital platforms and hinder adoption, particularly among underserved communities. Initiatives like Raast and the Digital Pakistan Vision showcase how robust cybersecurity measures can enhance user confidence, encouraging participation in online banking, e-governance, and e-learning. Qualitative methodology used in this study to explore, and describe cyber security and digital inclusion in Pakistan .Addressing cybersecurity issues like data breaches and online fraud is crucial to bridging the digital divide. The result of this study the interdependence of cybersecurity and digital inclusion, emphasizing Pakistan’s immediate needs: improving cybersecurity infrastructure, promoting digital literacy, and formulating policies tailored to local challenges. Ultimately, cybersecurity is not just a technical requirement but a foundation for sustainable digital inclusion. By protecting trust and enabling secure access, it accelerates digital transformation, empowers citizens, and reduces socio-economic disparities. The article recommends on policymakers, businesses, and stakeholders to collaborate in creating a secure and inclusive digital future for Pakistan.